Parthenium hysterophorus alleviates wilt stress in tomato plants caused by Ralstonia solanacearum through direct antibacterial effect and indirect upregulation of host resistance - Najeeb, Saba; Li, Yan (Frontiers in Plant Science, 2023)
Heavy damage to tomato crops due to wilt stress caused by pathogenic bacterium Ralstonia solanacearum and insufficient availability of management strategies with desired control level urged the researchers to investigate more reliable control methods to manage this issue in tomato and other horticultural crops. In this study, Parthenium hysterophorus, a locally and freely available herbaceous plant was successfully used to manage bacterial wilt of tomato. The significant growth reduction ability of P. hysterophorus leaves extract was recorded in agar well diffusion test and its ability to severally damage the bacterial cells was confirmed in SEM analysis. In both greenhouse and field trails, soil amended with P. hysterophorus leaves powder at 25g/Kg soil was found to effectively suppressed the pathogen population in soil and significantly reduced the wilt severity on tomato plants which resulted in increased growth and yield of tomato plants. The P. hysterophorus leaves powder at amount higher than 25g/Kg soil caused phytotoxicity to tomato plants. Results showed that P. hysterophorus powder applied at through mixing of soil at longer duration before transplanting tomato plants was more effective than mulching application and at shorter duration of transplantation. Lastly, the indirect effect of P. hysterophorus powder in managing bacterial wilt stress was evaluated through expression analysis of two resistance related genes PR2 and TPX. The upregulation of these two resistance related genes were recorded by the soil application P. hysterophorus powder. Findings of this study revealed the direct and indirect action mechanism of P. hysterophorus powder application to soil for the management of bacterial wilting stress in tomato plants and provide basis for including this technique as safe and effective management strategy to integrated disease management package.